2022
DOI: 10.3390/nursrep12020027
|View full text |Cite
|
Sign up to set email alerts
|

Before the COVID-Vaccine—Vulnerable Elderly in Homecare

Abstract: Background: At the beginning of 2020, the COVID-19 virus was spreading all over the world. Frail elderly were at risk for illness and death. Isolation seemed to be the best solution. The aim of this paper was to describe how the lockdown affected elderly homecare patients. Methods: We used an international self-reported screening instrument built on well-documented risk factors adapted to COVID-19. We considered ethical, legal, and practical concerns. The research included telephone interviews with 30 homecare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Te fndings from this study demonstrated a clear need for surveillance instruments to screen beyond COVID-19 symptoms given that few CSS clients had COVID-19 symptoms, but many had unmet needs that were exacerbated because of the pandemic measures. Tis is especially important for older adults and persons with disabilities who have unmet health-and social-care needs that are not known or addressed until a crisis point [19,37]. Te CVS has high potential for use to actively surveil vulnerable populations not only in future waves of the COVID-19 pandemic, but beyond, such as to identify isolated persons in the aftermath of environmental disasters relating to climate change [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te fndings from this study demonstrated a clear need for surveillance instruments to screen beyond COVID-19 symptoms given that few CSS clients had COVID-19 symptoms, but many had unmet needs that were exacerbated because of the pandemic measures. Tis is especially important for older adults and persons with disabilities who have unmet health-and social-care needs that are not known or addressed until a crisis point [19,37]. Te CVS has high potential for use to actively surveil vulnerable populations not only in future waves of the COVID-19 pandemic, but beyond, such as to identify isolated persons in the aftermath of environmental disasters relating to climate change [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…However, most surveillance tools that have been used during the pandemic only assess for COVID-19 symptoms and are lacking a way to identify and monitor the broader impact of the pandemic on older adults. In response to this limitation, the interRAI COVID-19 Vulnerability Screener (CVS) was developed by an international collaboration of researchers and care providers as a brief standardized screening instrument [18,19]. Te CVS was created based on two validated interRAI instruments (i.e., the interRAI Home Care and interRAI Check-Up) and a review of 15 international selfassessment tools for COVID-19 symptoms [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The isolation and uncertainty brought about by the pandemic have also significantly impacted mental health. Individuals who experienced isolation and uncertainty during the pandemic had higher levels of anxiety and depression compared to those who did not [ 27 , 28 ]. The quarantine measures and social distancing have also been linked to increased feelings of loneliness and social isolation, which can further exacerbate mental health problems [ 29 ].…”
Section: Psychological Consequences Of Covid-19mentioning
confidence: 99%
“…The government of Indonesia has implemented homecare measures to deal with COVID-19 patients (Nugroho & Wiseno, 2020). Due to potential underlying conditions, older patients are at a higher risk of infection due to the difficulty distinguishing COVID-19 symptoms from those associated with old age (Sørbye .et al, 2022). This is because community-acquired pneumonia in the elderly population has been found to decrease activities of daily living and quality of life, accompanied by a decrease in physical and mental function (Liu .et al, 2020).…”
Section: Introductionmentioning
confidence: 99%